2023
DOI: 10.1021/acsami.2c17005
|View full text |Cite
|
Sign up to set email alerts
|

Osteo-Immunomodulatory Role of Interleukin-4-Immobilized Plasma Immersion Ion Implantation Membranes for Bone Regeneration

Abstract: Barrier membranes for guided tissue regeneration are essential for bone repair and regeneration. The implanted membranes may trigger early inflammatory responses as a foreign material, which can affect the recruitment and differentiation of bone cells during tissue regeneration. The purpose of this study was to determine whether immobilizing interleukin 4 (IL4) on plasma immersion ion implantation (PIII)-activated surfaces may alter the osteo-immunoregulatory characteristics of the membranes and produce pro-os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
(71 reference statements)
2
3
0
Order By: Relevance
“…Macrophages were classically polarized into inflammatory phenotypes by LPS stimulation in vitro. 21 In this study, we observed that inflammatory macrophages treated with MDs-IL4 displayed markedly elongated cell morphologies compared to non-treated and MDs treated groups ( Figure 4A ), similar to the reports by other groups. 22 , 23
Figure 4 Immunoregulatory role of bioactive MDs-IL4 on inflammatory macrophages.
…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Macrophages were classically polarized into inflammatory phenotypes by LPS stimulation in vitro. 21 In this study, we observed that inflammatory macrophages treated with MDs-IL4 displayed markedly elongated cell morphologies compared to non-treated and MDs treated groups ( Figure 4A ), similar to the reports by other groups. 22 , 23
Figure 4 Immunoregulatory role of bioactive MDs-IL4 on inflammatory macrophages.
…”
Section: Resultssupporting
confidence: 89%
“…Macrophages were classically polarized into inflammatory phenotypes by LPS stimulation in vitro. 21 In this study, we observed that inflammatory macrophages treated with MDs-IL4 displayed markedly 4A), similar to the reports by other groups. 22,23 Next, we used qPCR to determine the relative gene expression of proinflammatory markers in different groups.…”
Section: Immunoregulatory Role Of Bioactive Mds-il4supporting
confidence: 91%
See 3 more Smart Citations